(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The last three years have been associated with a change in the status of social pedagogy as a branch of scientific knowledge and professional practice, as a result of which it was transferred from the pedagogical branch to the branch of social work. In addition, serious social changes in Ukraine, related both to the development of democracy in society, the implementation of humanitarian reforms, and the emergence of a number of social problems (war, population migration, poverty, the crisis of the family institution, etc.), indicate the need for changes in the field of professional assistance aimed at ensuring the psychological well-being of citizens. Today, there is some uncertainty regarding the main aspects of the profession of a social educator in society. But the content of this activity in the context of the deployment of professional practices in educational institutions, in particular in a secondary school, causes no less contradictions. The main idea is to autonomize the position of a social educator. A social educator should become a conductor of the philosophy and policy of the functioning of the educational environment, which is safe for the child, humanistically oriented, developing personal potential, providing appropriate material, physical, psychological, spiritual resources. His activities should be aimed at a critical assessment of the team’s progress towards progress, a clear response to the negative social influences of the educational environment on the personality of the child, participation in planning the impact of events on the personality of the child and the acquisition of a positive socialization experience. His mission is to improve the quality of human life through the harmonization of human-environment relations, and the goal of the activity is to create conditions for positive socialization and effective integration of man in society.